Cross-cultural adaptation and validation of Sarcopenia and Quality of Life (SarQoL) in Brazil - Orlandi, Fabiana de Souza; Nunes, Juliana Duarte; Santos, Diana Gabriela Mendes dos; Gratão, Aline Cristina Martins; Zazzetta, Marisa Silvana (São Paulo Medical Journal, 2023)
BACKGROUND: Sarcopenia is defined as a slow, progressive, and apparently inevitable process of involuntary loss of muscle mass, strength, and quality, which occurs with advancing age. It is widely accepted that sarcopenia can directly affect quality of life. OBJECTIVE: Translate, adapt and validate the “Sarcopenia and Quality of Life” instrument (SarQoL) to the Brazilian context. DESIGN AND SETTINGS: Translation, cross-cultural adaptation, and validation study carried out at the Federal University of São Carlos, São Carlos, São Paulo, Brazil. METHODS: The population consisted of 221 older adult participants. The steps recommended by the guidelines from the authors of the original instrument were followed sequentially: initial translation, synthesis of translations, backward translation, evaluation by a panel of judges, pre-test, and analysis of psychometric properties. The translation and adaptation process was conducted as recommended. RESULTS: Two hundred and twenty-one participants took part in the step analysis of the psychometric properties of SarQoL, in which 55 presented sarcopenia. Cronbach’s alpha coefficient of the total SarQoL questionnaire was 0.976, indicating excellent internal consistency. Excellent agreements between the test and retest with an Interclass Correlation Coefficient (ICC) of 0.983 (95% confidence interval: 0.901–0.996) were observed in the SarQoL domains. The domains of Short-Form 36 and EuroQoL 5-dimension showed significant correlation, from moderate to strong magnitude, with SarQoL total score, indicating convergent validity. CONCLUSION: The Brazilian version of SarQoL presented evidence of reliability and validity.